(untitled) (International journal of artificial intelligence, 2025)
In the article investment and innovation concepts in the economy theoretical and practical their place​​ each other connection , modern​ in the economy importance analysis In world experience used​ mechanisms , Uzbekistan​ in practice take going reforms and leather - fur in the industry investment-innovation strategies harmony​ issues illuminated .